Pendidikan gizi dengan media animasi dalam upaya memperbaiki kadar hemoglobin dan asupan gizi ibu hamil anemia - Novriani Tarigan; Sartini Bangun; Bernike Doloksaribu; Urbanus Sihotang (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
Nutrition education with animated media to improve hemoglobin levels and nutritional intake of anemic pregnant womenBackground: The prevalence of anemia among pregnant women in 2018 increased compared to 2013. Anemic pregnant women need to receive nutrition education. Nutrition education requires media and various studies that report the success of nutrition education using various media. Objective: This study aimed to analyze the effect of animated media nutrition education on improving hemoglobin and nutrient intake of anemic pregnant women. Methods: The study was quasi-experimental with a pretest-posttest one-group design on 31 anemic pregnant women. Nutrition education media, namely animated videos, were prepared based on interviews with cadres and pregnant women. Hemoglobin levels, knowledge, attitudes, iron tablet consumption compliance, and nutrient intake were measured before and after being given animated media nutrition education. Results: The mean hemoglobin level of pregnant women after the intervention increased by 1.75 g/dl; knowledge score 3.52; behavior score 4.06; iron tablet consumption 28 grains; energy intake 574.62 Kcal; protein intake 19.46 g; vitamin C intake 25.98 mg; and iron intake 3.17 mg. Conclusion: Nutrition education intervention using animated video can improve hemoglobin level, knowledge, attitude, iron tablet consumption, and nutritional intake of pregnant women.